2019
DOI: 10.1155/2019/1496535
|View full text |Cite
|
Sign up to set email alerts
|

Novel Models for the Prediction of Left Atrial Appendage Thrombus in Patients with Chronic Nonvalvular Atrial Fibrillation

Abstract: Predicting left atrial appendage thrombus (LAAT) in chronic nonvalvular atrial fibrillation remains challenging despite the fact that several predictive models have been proposed to date. In this study, we sought to develop new and simpler models for LAAT prediction in chronic nonvalvular atrial fibrillation. The study enrolled 144 patients with chronic nonvalvular atrial fibrillation who underwent transesophageal echocardiography for LAAT detection. We examined the association of LAAT incidence with the CHA2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…These results are in agreement with Do Van Chien et al, 18 who suggested that the diagnostic performance for LAA thrombus in patients with chronic nonvalvular AF may be higher when using the combination of LA deformation parameters than when using the CHA 2 DS 2 -VASc score alone.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with Do Van Chien et al, 18 who suggested that the diagnostic performance for LAA thrombus in patients with chronic nonvalvular AF may be higher when using the combination of LA deformation parameters than when using the CHA 2 DS 2 -VASc score alone.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, the CHA 2 DS 2 -VASc score needs to be improved and perfected. Van Chien et al has increased the predictive ability ( χ 2 ) from 3.53 to 33.48 by adding the left atrial volume index and the left atrial negative strain rate in the two-chamber view to the CHA 2 DS 2 -VASc score [ 31 ]. Similarly, predictive ability has increased by 13% when the left atrial emptying fraction is added to the CHA 2 DS 2 -VASc score, as shown in Kim et al's study [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found a positive correlation between LA size and the incidence of LAAT, although they excluded patients that were previously on anticoagulation (Van Chien et al, 2019). As described in the results, LA size greater than 4.48 cm was more likely to be associated with presence of LAAT.…”
Section: Re Sultsmentioning
confidence: 65%